2003
DOI: 10.1071/wr02043
|View full text |Cite
|
Sign up to set email alerts
|

Dispersal patterns in a regional koala population in south-east Queensland

Abstract: Koala dispersal was investigated as part of a detailed ecological study of a nationally significant koala population located 20 km south-east of Brisbane, Queensland. From 1996 to 2000, 195 koalas from three sites were captured and fitted with radio-collars. A total of 40 koalas (23 males and 17 females) dispersed from these sites. Most (93%) dispersing individuals were 20–36 months of age. Three adult females (more than 36 months old) dispersed and no adult males dispersed during the study. A significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
67
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 0 publications
5
67
0
Order By: Relevance
“…Our findings are consistent with other studies that have shown a high probability of trauma for koalas moving in and through fragmented and heavily urbanised areas in south-east Queensland (e.g. Dique et al 2003aDique et al , 2003c. One of the koalas that was killed by a train (F2) had crossed the rail line by climbing over chainwire fencing while a safe underpass under the rail line for pedestrians was within metres of the animal's crossing point.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our findings are consistent with other studies that have shown a high probability of trauma for koalas moving in and through fragmented and heavily urbanised areas in south-east Queensland (e.g. Dique et al 2003aDique et al , 2003c. One of the koalas that was killed by a train (F2) had crossed the rail line by climbing over chainwire fencing while a safe underpass under the rail line for pedestrians was within metres of the animal's crossing point.…”
Section: Discussionsupporting
confidence: 82%
“…Unlike other species of animals that rely on closed canopies, understorey or ground cover to move between habitat (e.g. lemuroid ringtail possum, Hemibelideus lemuroides: Wilson et al 2007; the bush rat and the brown antechinus: Strevens 2007), this study is consistent with other radio-tracking studies that monitored koalas that were able to navigate across roads, cleared areas and other less permeable natural and artificial landscape features (Dique et al 2003c;Thompson 2006). Again, a longer study with more detailed monitoring of the behaviour of collared koalas may highlight the reason for the perceived barrier that structures such as koala-climbable fencing pose to some animals and not others.…”
Section: Discussionsupporting
confidence: 78%
“…There is little evidence for longer movements in most cases ), though dispersing individuals, mostly young males, may occasionally cover distances of several kilometres over land with little vegetation. In south east Queensland, the average distance between natal and breeding home ranges was similar for males and females, at approximately 3.5 km (Dique et al 2003b). Maximum dispersal distances were up to approximately 10 km for males and females (Dique et al 2003b).…”
Section: Movement/dispersalmentioning
confidence: 89%
“…In south east Queensland, the average distance between natal and breeding home ranges was similar for males and females, at approximately 3.5 km (Dique et al 2003b). Maximum dispersal distances were up to approximately 10 km for males and females (Dique et al 2003b). Other studies have reported moves of up to 11 km in Tucki Tucki Reserve in New South Wales (Gall 1980) and 16 km in rural south east Queensland (White 1999).…”
Section: Movement/dispersalmentioning
confidence: 89%
“…Road mortality is recognized as one of the major causes of mortality in this koala population (Dique et al 2003b, Rhodes et al 2011) with an average of nearly 300 deaths a year (Dique et al 2003b) in southeast Queensland. About half of the deaths of dispersing individuals are due to vehicle collisions (Dique et al 2003a) with risk of collision increasing with both traffic volume and speed (Dique et al 2003b). Additionally, roads were found to be a key barrier to genetic flow in the southeast Queensland koala population (Dudaniec et al 2013).…”
Section: Study Areamentioning
confidence: 99%